Factors that influence on the decisions of battered women - Juana Robledo Martín; Diana de la Fuente Aparicio; Ana Belén Salamanca Castro; Sara Sánchez Castro (Fundación para el Desarrollo de la Enfermería, 2008)
Violence towards and against women consists in any kind of violation of woman's personality, her physical integrity or her freedom of movement. Nowadays, gender-based violence is considered a state and public health problem as well as a social concerning subject.Objective: To identify the factors that influence on the decisions that battered women make.Methodology: The study population are battered women who live in Madrid province and who are being attended in the Municipal Points of the Regional Observatory against the Gender Violence.The information was collected by performing focus groups and deep interviews.Results: There are several factors which influence on the decisions that battered women make, like the existence or not of children they have to take care of, the economic dependence and the ignorance of the woman, in some cases, of the existence of this ill-treatment, but over all, we could even say beyond all these, there is one that is the most important, common and we could say it is the main axis that determine their behaviour. This factor is fear.Discussion: When attending these women we may be aware of the psychological situation they are, and we should be able to identify if the woman is asking us for help when she comes to us and try to identify and treat this factor that influences the decisions the woman we attend makes.